2017
DOI: 10.1111/jasp.12459
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype content of people with acquired brain injury: Warm but incompetent

Abstract: Since stereotypes about people with acquired brain injury (ABI) can lead to prejudice, studying these stereotypes is highly important. In two studies, we examined these stereotypes both on idiosyncratic dimensions and on the two dimensions of the Stereotype Content Model. Participants completed a specific questionnaire about ABI and warmth and competence questionnaires regarding people with ABI and other social groups. Specific stereotypes about ABI were found to be underpinned by dimensions of "cognitive impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 73 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…According to Fiske et al (2002), paternalized groups elicit pity and sympathy (Collange et al, 2009;Cottrell & Neuberg 2005;Fiske et al, 2002). Thus, some disadvantaged groups, such as people with disabilities, are perceived as warm, but at the same time as incompetent (Carlsson & Björklund, 2010;Cuddy, Fiske, & Glick, 2008;Cuddy et al, 2009;Durante, Volpato, & Fiske, 2010;Fresson, Dardenne, Geurten, & Meulemans, 2017). In other words, nowadays, people with disabilities, with the exception, perhaps, of the most stigmatized groups such as those with mental illness (Araten-Bergman & Werner, 2017;Follmer & Jones, 2017;Jahoda & Markova 2004;Oexle, Müller, et al, 2017;, are generally accepted and their fundamental rights recognized, at least in Western society.…”
Section: Palabras Clavementioning
confidence: 99%
“…According to Fiske et al (2002), paternalized groups elicit pity and sympathy (Collange et al, 2009;Cottrell & Neuberg 2005;Fiske et al, 2002). Thus, some disadvantaged groups, such as people with disabilities, are perceived as warm, but at the same time as incompetent (Carlsson & Björklund, 2010;Cuddy, Fiske, & Glick, 2008;Cuddy et al, 2009;Durante, Volpato, & Fiske, 2010;Fresson, Dardenne, Geurten, & Meulemans, 2017). In other words, nowadays, people with disabilities, with the exception, perhaps, of the most stigmatized groups such as those with mental illness (Araten-Bergman & Werner, 2017;Follmer & Jones, 2017;Jahoda & Markova 2004;Oexle, Müller, et al, 2017;, are generally accepted and their fundamental rights recognized, at least in Western society.…”
Section: Palabras Clavementioning
confidence: 99%
“…This suggests a role for community or peer education about brain injury and how to support interactions that promote, rather than undermine, dignity (Stiekema, Winkens, Ponds, De Vugt, & Van Heugten, 2020). The idea that the general public and even health professionals may hold negative stereotypes about people who have had brain injury is not new (Fresson et al, 2017;Linden & Crothers, 2006;McLellan et al, 2010;Nochi, 1998;Slettebø, Caspari, Lohne, Aasgaard, & Nåden, 2009). Several authors have also identified how such views can negatively impact the injured person's experience when accessing services (Redpath et al, 2010).…”
Section: Discussionmentioning
confidence: 99%